Isolation and Characterization of Endophytic Fungi in Ramin (Gonystylus bancanus Miq. Kurz) from Central Kalimantan - Faridah Tsuraya; Rahayu Opi Anggoro; Adi Jaya; Siti Sunariyati; Febri Nur Ngazizah (Jurnal Biologi Tropis, 2026)
Ramin (Gonystylus bancanus Miq. Kurz) is one of the typical woody plants that live in peat swamp forest ecosystems, especially in Central Kalimantan. Ramin plants have endophytic fungi that live in plant cells that can contaminate tissue culture propagation. In addition, endophytic fungi in ramin plants have not been widely studied, both in terms of characterization and potential. This study aimed to identify and analyze endophytic fungi residing in ramin plants. The methods used were media preparation and tool preparation, isolation of endophytic fungi, macro- and microscopic characterization of endophytic fungi, and data analysis. This study successfully isolated five endophytic fungi from G. bancanus plants, including 4 isolates (BR1, BR2, BR3, BR4) derived from stems and 1 isolate (BDR) derived from stems and leaves. The characters of these endophytic fungi are white and black in color, smooth and rough texture, and hyphae with and without hyphae (asepta). Endophytic fungi in ramin plants pose a challenge for propagating ramin tissue culture because they become contaminants. However, endophytic fungi certainly have their own benefits in the bodies of ramin plants and other potential benefits for humans. This research can serve as an initial study to determine the potential of endophytic fungi in ramin plants and to provide new information on handling contaminants in ramin plant tissue culture.